Study the antinociceptive effect of the Zingiber officinale ethanolic extract and Vitamin C in rats - AL- Shebani, Wisam. H. S. (The Iraqi Journal of Veterinary Medicine, 2010)
The present study was designed to investigate the antinociceptive activity of seperate andcombined treatments of ethanol extract of Zingiber officinale rhizomes and vitamin C onvisceral nociception induced by intraperitoneal injection of 2% acetic acid which producedwrithing in rats. The preliminary chemical tests were performed on the extract and revealed thepresence of flavanoids, alkaloids and tannins. Visceral nociceptive responses including thelatency time to beginning of the first writhe, number of writhes per hour and the inhibitionpercentage of writhing. Seperate i. p. injection of ethanol extract of Zingiber officinale at dose of25 and 50 mg/kg BW caused significant (P<0.01) increase in latency time and significant(P<0.01) reduction in writhing number. Seperated i. p. injection of vitamin C at dose of 10mg/kg BW caused significant (P<0.05) reduction in writhing number, whereas, i. p injection ofvitamin C at dose of 15 mg/kg BW produced significant prolongation in latency time andreduction in writhing number (P<0.01). Combined treatment with ethanol extract ofZingiber officinale at dose of 25 mg/kg BW and vitamin C at dose of 10 mg/kg BW. i.p.produced significant suppression (P<0.01) in pain responses as compared with the effect of thesame doses when used each seperately. It is concluded that both ethanol extract of Zingiberofficinale rhizomes and vitamin C are able to suppress visceral pain, and vitamin C potentiatesthe antinociceptive effect of the ethanol extract of Zingiber officinale rhizomes